Spatial Patterns of Organic and Inorganic Carbon in Lake Qinghai Surficial Sediments and Carbon Burial Estimation - Chen, Xi; Meng, Xianqiang; Song, Yinxian; Zhang, Bin; Wan, Zhiwei; Zhou, Bingqing; Zhang, Enlou (Frontiers in Earth Science, 2021)
Lake carbon burial is of vital significance in global carbon cycle and carbon budget, particularly in the large deep-water lakes. However, carbon burial in large deep-water lakes is hard to estimate due to the difficulty in obtaining high spatial-resolution samples. In this study, we investigated distributions of total organic carbon (TOC) and inorganic carbon (TIC), two main carbon components in lake sediments, based on dozens of surficial sedimentary samples (n=26) covering whole Lake Qinghai, the largest saline lake in China. The results showed that TOC content, with a range of 1.4%-4.8%, was significantly higher in the lake area near the northern lakeshore where human activities are concentrated, lower in the lake areas near the Buha River mouth and eastern lake area. In contrast, TIC content, ranging from 1.5% to 3.8%, increased from the northwestern and southeastern lake areas toward the lake center, and mainly depended on hydro-chemical and hydraulic characteristics. The inorganic carbon burial (47.77±19.73 Gg C yr-1) was approximately equal to organic carbon burial (47.50±22.68 Gg C yr-1) and accounted for about 50% of the total carbon burial (95.27± 37.74 Gg C yr-1), suggesting that saline lakes constitute a large inorganic carbon pool in addition to an organic carbon pool. Because of saline water body type in arid and semiarid regions and alpine Qinghai-Tibet Plateau, lakes in these regions have huge inorganic carbon burial potential and important contribution in global carbon budget.